Organometallic Compounds in Cancer Therapy: Past Lessons and Future Directions - Martins, Pedro; Marques, Mara; Coito, Lidia; J.L. Pombeiro, Armando; Viana Baptista, Pedro; R. Fernandes, Alexandra (Anti-Cancer Agents in Medicinal Chemistry, 2014)
Over the past few years, modern medicinal chemistry has evolved towards providing us new and alternative chemotherapeutic compounds with high cytotoxicity towards tumor cells, alongside with reduced side effects in cancer patients. Organometallic compounds and their unique physic-chemical properties typically used in homogenous catalysis are now being translated as potential candidates for medical purposes. Their structural diversity, ligand exchange, redox and catalytic properties make them promising drug candidates for cancer therapy. Over the last decade this area has witnessed a steady growth and a few organometallic compounds have in fact already entered clinical trials, emphasizing its increasing importance and clinical relevance. Here we intend to stress out the different applications of organometallic compounds in medicine with emphasis on cancer therapy, as well as address setbacks regarding formulation issues, systemic toxicity and off-target effects. Advantages over classical coordination metal complexes, their nanovectorisation and specific molecular targets are also discussed.Cancer therapy, clinical trials, M-arenes, M-carbenes, M-carbonyls, metallocenes, nanovectorisation, organometallics compounds.
Keywords: nanovectorisation